Thermally Stable Schiff Base and its Metal Complexes: Molecular Docking and Protein Binding Studies - Kamaci, Umran Duru; Kamaci, Musa; Peksel, Aysegul (SPRINGER/PLENUM PUBLISHERS, 2017)
In this paper, interaction of Schiff base and its metal complexes carrying naphthalene ring in the structure with bovine serum albumin (BSA) were investigated using UV-vis absorption, fluorescence spectroscopies and molecular docking methods. The effect on the binding mechanism and properties of these compounds containing metal-free, iron and copper ions were also investigated. The fluorescence spectroscopy results showed that fluorescence intensity of BSA in the presence of different concentration of ligands was decreased through a static quenching mechanism. Binding constants (KSV, Kbin and Ka) and thermodynamic parameters (Delta G, Delta H and Delta S) for the ligand-protein interactions were also determined. Delta G values of ligand-protein interaction were calculated in the range - 6.3 to -5.5 kcal/mol. These negative values showed that binding process is spontaneous and, hydrogen bonding and van der Waals force were main interaction of the protein and ligands. Delta H and Delta S value were also calculated in the range of 1.10 to 1.26 kJ/mol and 0.133 to 0.135 kJ/mol. K, respectively. These positive values indicated that the binding process between ligands and BSA are endothermic and electrostatic interaction, respectively.
Keywords: Protein binding; Molecular docking; Metal complexes; Bovine serum albumin; Thermally stable Schiff base; BOVINE SERUM-ALBUMIN; LIGAND; DNA; FLUORESCENCE; ANTIOXIDANT; MECHANISM; SENSOR; CU2+; Biochemistry & Molecular Biology; Chemistry